2021
DOI: 10.21037/atm-21-1162
|View full text |Cite
|
Sign up to set email alerts
|

The margin of internal risk volume on atrial septal and ventricular septal based on electrocardiograph gating 4DCT

Abstract: Background: The aim of this study was to quantify the margin of internal risk volume (IRV) on the atrial septum (AS) and ventricular septum (VS) based on electrocardiograph gating (ECG-gating) 4DCT.Methods: Twenty patients were enrolled and received an ECG-gating 4DCT scan performed in breathhold, and CT images were reconstructed at 5% intervals of the cardiac cycle for a total of 20 phases (0-95%).The contouring of the AS and VS were delineated in each phase, and the displacements and margin of the AS and VS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study found that the left anterior descending and left circumflex coronary arteries exhibited significant motion in the head-foot direction relative to the LR and front-back directions, which is comparable with the results of the present study. Li et al [ 17 ] identified larger motion amplitudes in the AP and head-foot directions of the AS than those of the VS in their AS study. This finding aligns with the observed motion patterns of the VS and AS in response to heartbeats during the three breathing states evaluated in this research.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the left anterior descending and left circumflex coronary arteries exhibited significant motion in the head-foot direction relative to the LR and front-back directions, which is comparable with the results of the present study. Li et al [ 17 ] identified larger motion amplitudes in the AP and head-foot directions of the AS than those of the VS in their AS study. This finding aligns with the observed motion patterns of the VS and AS in response to heartbeats during the three breathing states evaluated in this research.…”
Section: Discussionmentioning
confidence: 99%